2013
DOI: 10.1007/s11914-012-0132-1
|View full text |Cite
|
Sign up to set email alerts
|

The Potential Benefits and Inherent Risks of Vibration as a Non-Drug Therapy for the Prevention and Treatment of Osteoporosis

Abstract: The delivery of mechanical signals to the skeleton using vibration is being considered as a non-drug treatment of osteoporosis. Delivered over a range of magnitudes and frequencies, vibration has been shown to be both anabolic and anti-catabolic to the musculoskeletal tissues, yet caution must be emphasized as these mechanical signals, particularly chronic exposure to higher intensities, is a known pathogen to many physiological systems. In contrast, accumulating preclinical and clinical evidence indicates tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
74
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 56 publications
(74 citation statements)
references
References 73 publications
(79 reference statements)
0
74
0
Order By: Relevance
“…Acceleration has been proposed as an alternate mechanical signal sensed by cells during LMHF vibration 13,55 . However, results here show that acceleration varied little with the loaded samples; a minimum value within the marrow was found to be 0.15 g, with the majority of the marrow experiencing the applied 0.3 g. Therefore, trying to determine whether a relationship between bone formation, or other parameters, and acceleration exists was not possible with the current results.…”
Section: Discussionmentioning
confidence: 99%
“…Acceleration has been proposed as an alternate mechanical signal sensed by cells during LMHF vibration 13,55 . However, results here show that acceleration varied little with the loaded samples; a minimum value within the marrow was found to be 0.15 g, with the majority of the marrow experiencing the applied 0.3 g. Therefore, trying to determine whether a relationship between bone formation, or other parameters, and acceleration exists was not possible with the current results.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have reported that mechanical signals are directly recognized by mesenchymal stem cells (MSCs), and serve to promote osteoblastogenesis and inhibit adipogenesis, even under environmental conditions inducing fat formation (Chan et al. ). Despite general agreement that mechanical signals play a central role in fat distribution, the ideal characteristics of an effective loading regimen or the molecular cues that control the adaptive responses are still poorly understood (Engler et al.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, we investigated the effects of ET associated with low-intensity and high-frequency MV on bone tissue of osteopenic female mice, a classic animal model of postmenopausal osteoporosis (Nakamura et al 2007;Li et al 2010;Syed et al 2010;Ozturan et al 2011;Chan et al 2013;Florencio-Silva et al 2013;Santos et al 2014;Pacheco-Costa et al 2015).…”
Section: Discussionmentioning
confidence: 99%
“…LMMS is thought to have the most robust effect on the skeleton before physical maturity [30]. Previous studies of individuals with cerebral palsy [31,32], thalassemia [33], post-menopausal osteoporosis [34][35][36], and young females with a history of fracture [37] have shown that LMMS increases BMD and improves bone quality and quantity.…”
Section: Lmms and Bone Healthmentioning
confidence: 99%